Natural Products and their Role in the Management of Rheumatoid arthritis: A Review of Current Evidence - M.Mohammed Lukman,; P.Gowthaman,; S.Anbazhagan,; S.Karthika,; K.Yuvarani,; B.Sathya,; S.A.Vadivel, (Asian Journal of Pharmaceutical Research and Development, 2025)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disorder characterized by persistent joint inflammation, pain, and progressive cartilage and bone damage. Conventional pharmacological treatments, such as nonsteroidal anti-inflammatory drugs (NSAIDs) and disease-modifying antirheumatic drugs (DMARDs), provide symptomatic relief but are associated with adverse effects and long-term management challenges. Consequently, natural products have gained attention as alternative or complementary therapeutic agents due to their anti-inflammatory and immunomodulatory properties. Aim: This review examines the potential of natural products in managing RA by targeting key inflammatory pathways and oxidative stress, with a focus on bioactive compounds such as flavonoids, terpenoids, alkaloids, and polyphenols. Methods: A comprehensive literature review was conducted to evaluate preclinical and clinical studies on the efficacy of natural products in RA treatment. The mechanisms of action, bioavailability concerns, and potential combination therapies were analyzed. Results: Compounds such as curcumin, resveratrol, Boswelliaserrata, and ginger have demonstrated significant anti-inflammatory and immunomodulatory effects in RA models. These natural products regulate cytokine production (TNF-α, IL-6), inhibit cyclooxygenase (COX), and mitigate oxidative stress, offering multi-targeted therapeutic potential. However, challenges such as poor bioavailability and variability in composition necessitate advanced formulations and standardization. Conclusion: Natural products provide a promising adjunct in RA management. While clinical evidence supports their efficacy, further research, large-scale clinical trials, and standardized formulations are crucial for their integration into clinical practice.